A cephalometric comparison of mandibular headgear and chin-cap appliances in orthodontic and orthopaedic view points - (:unkn) unknown (My University, 1994)
In this study, the clinical effects of two extra-oral orthopaedic appliances were compared cephalometrically. Lateral cephalograms of 60 individuals were used in this investigation. The study group was randomly divided into three parts as a) control, b) mandibular headgear and c) chin-cap groups. The subjects of the study group were selected among Class III, low angle or vertically normally growing individuals. The total observation period was one year. Results showed that both appliances were effective skeletally, but there were some differences between them. The results are as follows; chin-cap therapy led to an inhibition in the development of the upper face and an effective control of the vertical dimension in addition to the posterior positioning of the mandible. Mandibular headgear inhibited general growth and development of the mandible and showed an increase in lower anterior face height and also, a significant lower molar distalization was found.
Keywords: Female; Humans; Male; Child; Cephalometry; Time Factors; Statistics, Nonparametric; Malocclusion, Angle Class III; Prognathism; Evaluation Studies as Topic; Extraoral Traction Appliances